AT1-AA (Angiotensin II Type 1 Receptor Agonistic Autoantibody) Blockade Prevents Preeclamptic Symptoms in Placental Ischemic Rats. Issue 5 (May 2018) - Cunningham, Mark W.; Castillo, Javier; Ibrahim, Tarek; Cornelius, Denise C.; Campbell, Nathan; Amaral, Lorena; Vaka, Venkata Ramana; Usry, Nathan; Williams, Jan M.; LaMarca, Babbette
Abstract : Women with preeclampsia produce AT1-AA (agonistic autoantibodies to the angiotensin II type 1 receptor), which stimulate reactive oxygen species, inflammatory factors, and hypertensive mechanisms (ET [endothelin] and sFlt-1 [soluble fms-like tyrosine kinase-1]) in rodent models of preeclampsia. The placental ischemic reduced uterine perfusion pressure (RUPP) rat model of preeclampsia exhibits many of these features. In this study, we examined the maternal outcomes of AT1-AA inhibition (‵n7AAc′) in RUPP rats. Blood pressure was higher in RUPP rats versus normal pregnant (NP) rats (123±2 versus 99±2 mm Hg, P <0.05), which was reduced in RUPP+‵n7AAc′ (105±3 versus 123±2 mm Hg, P <0.05 versus RUPP). Uterine artery resistant index was increased in RUPP versus NP rats (0.71±0.02 versus 0.49±0.02, P <0.05) and normalized in RUPP+‵n7AAc′ rats (0.55±0.03). Antiangiogenic factor sFlt-1 was elevated in RUPP versus NP rats (176±37 versus 77±15 pg/mL, P <0.05) but normalized in RUPP+‵n7AAc′ (86±9, P =0.05 versus RUPP). Plasma nitrate and nitrite were decreased (14±1 versus 20±1 µMNO3, P <0.05) and isoprostanes were elevated (20 117±6304 versus 2809±1375 pg/mL, P <0.05) in RUPP versus NP rats; and normalized in RUPP+‵n7AAc′ rats; (18±2 µMNO3 ; 4311±1 pg/mL). PPET-1 (preproendothelin-1) expression increased 4-fold in RUPP versus NP rats which were prevented with ‵n7AAc′. Importantly, placental cytolytic natural killer cells were elevated in RUPP versus NP rats (8±2% versus 2±2% gated, P <0.05), which was prevented in RUPP+‵n7AAc′ total (3±1% gated, P <0.05) In conclusion, AT1-AA inhibition prevents the rise in maternal blood pressure and several pathophysiological factors associated with preeclampsia in RUPP rats and could be a potential therapy for preeclampsia.